Phage typing of Salmonella enteritidis in the United States. - Hickman-Brenner, F W (1991)
The number of reported isolates of Salmonella enteritidis has increased dramatically in the last 10 years. For many years phage typing has been a useful epidemiologic tool for studying outbreaks of S. typhi and S. typhimurium. In 1987, Ward et al. (L. R. Ward, J. De Sa, and B. Rowe, Epidemiol. Infect. 99:291-294, 1987) described a phage typing scheme for S. enteritidis. This system differentiated 27 phage types by use of 10 typing phages. With these phages, we typed 573 strains of S. enteritidis from humans (42 outbreaks), animals, food, and the environment. Ninety-six percent of the strains were typeable. The most common phage types were 8 (48.2%), 13a (20.1%), 13 (7.8%), and 14b (7.8%). Most of the strains were specifically collected from egg-related outbreaks in the northeastern United States in 1988 and 1989, probably accounting for the distribution of the four most common types in this sample. This system was particularly useful for differentiating a group of animal strains that had a number of diverse phage types. For 49 animal strains typed, 16 different patterns were obtained. Phage type 8 represented 32% of these strains, but no other phage type represented more than 8% of these strains. One-half of the 16 animal strains that were phage type 8 were from poultry. This phage typing system will be useful for comparing phage types found in the United States with those types encountered worldwide and for determining whether virulent strains of phage type 4 are entering the United States. Additional phage typing systems as well as molecular techniques are being studied to determine whether they can differentiate strains of phage types 8 and 13a.